Monitoring the epidemic process at geohelminthism among children in Rivne region - R.R. Drab; I.V. Guschuk; R.V. Safonov; A.V. Byalkovsky; O.I. Brezetska (Zaslavsky O.Yu., 2017)
Background. High prevalence of geohelminthism among children in the world, the country, Rivne region, their invasiveness and dangerous influence on the children's organism, long-term presence in the host organism, ability to survive determine the relevance of the problem of helminthism. Helmints are transmitted through environmental objects, the level of contamination of which is crucial in the study of the child population's incidence. The objective of the study was epidemiological monitoring of the peculiarities of geohelminthiasis incidence among children in Rivne region and environmental factors contaminations with helmints eggs. Materials and methods. Over 2012-2016 there were studied 8861 foci of ascariasis, 116 trichurosis, 142 toxo- cariasis in different age groups and contingents; a sanitary-parasitological study of 25,812 epidemiologically important environmental factors was carried out. Results. A high intensity of the epidemiological process for ascariasis among the children of Rivne region (649.29 per 100,000 population) was found, being highest in the age group 5-9 years (1095.98 per 100,000 population), with a tendency to increase among pre-school children. Despite the decrease in trichurosis indice, incidence rates in children aged 5-9 years remain high (20.11 per 100,000 population). A sharp toxocariasis increase in children (from 8.47 to 16.83 per 100 thousand of the population), mainly schoolchildren (57.0 %) causes concern due to aggressive invasions course. A high level of environmental contamination with helmints eggs through vegetables, soil, sewage, soil from micro-foci of geohelminthiasis, water from open reservoirs proves their importance as factors of transmission and maintenance of these invasions. Conclusions. The epidemiological status of Rivne region territory in terms of geohelminthism is defined as endemic; a situational analysis of the incidence in children aged 0-17 years with geohelminthiasis was conducted and the role of the environmental contamination as a factor of the transmission of these infestations was determined.